Keterlibatan Penyuluh Agama Islam Dalam Mengurangi Angka Perceraian di Desa Selogudik Kecamatan Pajarakan Kabupaten Probolinggo - Adnan Quthny, Abu Yazid; Fathullah (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
Abstract In this research is how the position of the Extension of the Religion of Islam in minimizing the formation of divorce in the Village Selogudik District Pajarakan Probolinggo Regency. The extension of religion as the religious leaders required in order to able to deploy all aspects of construction through the door of religion so that counseling can be successful, until someone religious educator can master module of propaganda, the ordinances of the da'wah and extension method, so that one religious educator is expected to achieve the purpose of da'wah is can give new insights to the community towards a better life and a prosperous born or inner. This study is expected to be able to share contributions or enrich the concepts, the theories of the science of research that is suitable to the field of science in something to research as well as research results is expected to be able to share the input to the community special Religious Educator. The research uses field research( field research). Primary information source is the main information obtained directly from the field. In this research the primary information source shaped the results of interviews with Religious Educator KUA Kecamatan Pajarakan, the Head of the Village Selogudik, Religious leaders, community leaders of the Village Selogudik, people which parted as well as people who are not up to the split in the Village Selogudik. On the contrary a source of secondary information is reported, the daily, as well as books that support this research. All the information is systematically compiled, reviewed, after which it is drawn a conclusion in conjunction with the problems in the meticulously. The results of the research show that the position of the Extension of the Religion of Islam in minimizing the formation of divorce in the Village Selogudik District Pajarakan Probolinggo Regency has not been optimally perform their duties. This can be seen from the results of the research if that is so obstacle is the lack of public knowledge about the task and the position of the Extension of the Religion of Islam. So there is still very little companion husband and wife who were about to leave come and ask for advice to the Extension of the Religion of Islam. Dalam riset ini merupakan bagaimana kedudukan Penyuluh Agama Islam dalam meminimalisir terbentuknya perceraian di Desa Selogudik Kecamatan Pajarakan Kabupaten Probolinggo. Penyuluh agama selaku pemuka agama dituntut supaya sanggup menyebarkan seluruh aspek pembangunan lewat pintu agama supaya penyuluhan bisa sukses, hingga seseorang penyuluh agama bisa menguasai modul dakwah, tata cara dakwah serta metode penyuluhan, sehingga seseorang penyuluh agama diharapkan bisa menggapai tujuan dakwah ialah bisa memberi wawasan baru kepada masyarakat kearah kehidupan yang lebih baik serta sejahtera lahir ataupun batin. Keywords: Involvement of the Religious Educator, Divorce